2020
DOI: 10.1039/d0ay01241f
|View full text |Cite
|
Sign up to set email alerts
|

A turn-on fluorescent sensor based on carbon dots from Sophora japonica leaves for the detection of glyphosate

Abstract: A green synthesis carbon dots (CDs) with low cost and low toxicity was applied to establish fluorescent nanoprobe for measurement of glyphosate. The synthesis was realized by one-pot hydrothermal procedure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…[27] The O1s spectrum ( Figure 2d) showed three peaks at 530.6, 531.5 and 532.3 eV which proved the existence of OÀ H, C=O and CÀ OH. [28][29][30] The results confirmed the presence of oxygen-and nitrogen-containing groups on the surface of CDs.…”
Section: Characterization Of Cdssupporting
confidence: 52%
See 1 more Smart Citation
“…[27] The O1s spectrum ( Figure 2d) showed three peaks at 530.6, 531.5 and 532.3 eV which proved the existence of OÀ H, C=O and CÀ OH. [28][29][30] The results confirmed the presence of oxygen-and nitrogen-containing groups on the surface of CDs.…”
Section: Characterization Of Cdssupporting
confidence: 52%
“…Two peaks in the N1s spectrum (Figure 2c) could be attributed to C−N−C (399.3 eV) and N−H (400.1 eV) [27] . The O1s spectrum (Figure 2d) showed three peaks at 530.6, 531.5 and 532.3 eV which proved the existence of O−H, C=O and C−OH [28–30] . The results confirmed the presence of oxygen‐and nitrogen‐containing groups on the surface of CDs.…”
Section: Resultsmentioning
confidence: 89%
“…The spectral properties of NRNC-CDs were shown in Fig.2A. The UV-Vis absorption band was observed at 270 nm, which was contributed to the π−π * transition of C=C on the surface of CDs [14]. The excitation and emission uorescence spectrum of NRNC-CDs indicated that the maximum excitation exhibited at 354nm and the maximum emission at 456 nm.…”
Section: Characterization Of the Nrnc-cdsmentioning
confidence: 97%
“…Another example using carbon quantum dots was reported by Hou et al, in which iron (III) cations were used as fluorescence quenchers (Hou et al, 2020). Subsequent introduction of glyphosate resulted in strong interactions between the glyphosate and the iron (III) cations, which removed the cations from the proximity of the carbon dots and restored the fluorescence.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Although such pesticide-induced fluorescence quenching enables high performance sensors, there are situations in which turn-on fluorescence sensors for pesticides might be more beneficial. Efforts to address this issue are ongoing, and include the use of pesticide-induced disruption of electron transfer that restores the electron donor's innate luminescence (Hou et al, 2020). More broadly, efforts to solve unsolved challenges in fluorescencebased pesticide detection are expected to lead to future developments and significant advances in pesticide research.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%